2020
DOI: 10.3389/fendo.2020.00005
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Relevance of Hyperkyphosis: A Narrative Review

Abstract: The kyphosis angle of the thoracic spine tends to increase with aging. Hyperkyphosis is a kyphosis angle, exceeding the normal range. This narrative literature review aims to provide an overview of the current literature concerning kyphosis measurement methods, the etiology and adverse health effects of hyperkyphosis. As of yet, a well-defined threshold for hyperkyphosis is lacking. To attain more generalizability and to be able to compare study results in older adults, we propose to define age-related hyperky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 71 publications
2
62
0
1
Order By: Relevance
“…Although thoracic and thoracolumbar hyperkyphosis increases the risk of future spine fracture in patients with previous fractures [24], the neutral posture for radiographic evaluation may be insu cient to describe the internal mechanical state of vertebral compression fractures. Previous studies ran a spinal simulation in vertical and neutral mechanical states, but most low-energy spinal injuries are caused in the lumbar hyper exion posture [9,10].…”
Section: Resultsmentioning
confidence: 99%
“…Although thoracic and thoracolumbar hyperkyphosis increases the risk of future spine fracture in patients with previous fractures [24], the neutral posture for radiographic evaluation may be insu cient to describe the internal mechanical state of vertebral compression fractures. Previous studies ran a spinal simulation in vertical and neutral mechanical states, but most low-energy spinal injuries are caused in the lumbar hyper exion posture [9,10].…”
Section: Resultsmentioning
confidence: 99%
“…13 Since it was hard to nd out whether a patient was known to have one of these conditions, in the absence of a complete medical history, it was di cult to differentiate. However, different studies have shown that kyphosis is also associated with a poor prognosis 17,18,19 . This could make the differentiation less relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperkyphosis is present when the kyphosis angle exceeds over 50 degree. 1,2 There are several methods used to measure thoracic kyphosis. The standard method is the Cobb angle, which is measured from a lateral radiograph as the angle subtended by the vertebral endplates above and below the curve.…”
Section: Introductionmentioning
confidence: 99%